(untitled) (Hematology Meeting Reports, 2009)
Introduction Multiple myeloma (MM) is a hematological malignancy of plasma cells that is characterized by clonal expansion, bone marrow infiltration, hypercalcemia, renal insufficiency, and the presence of immunoglobulin paraproteins in the serum and urine in the vast majority of patients (Blade et al. 1998). The disease arises from a B-cell of the normal germinal center as a result of a chromosomal translocation that places an oncogene under the control of immunoglobulin enhancers (Kuehl & Bergsagel 2002). In the US, MM is the second most common hematological malignancy after non-Hodgkin’s lymphoma with approximately 20,000 new cases each year (Jemal et al. 2008). It has remained incurable, with a reported median survival of 3–4 years and a 5-year relative survival of approximately 33% (Greipp et al. 2005; ACS 2007). Prior approaches to treatment, including high dose therapy, have prolonged survival in MM, although remissions are inevitably followed by relapse (Blade et al. 1998). Previously, the aims of treatment were to control disease by safely achieving a sequence of durable responses, without compromising quality of life (Smith et al. 2006). Novel therapies, including lenalidomide, thalidomide and bortezomib, have transformed the clinical management of MM and are increasingly recognized as potent therapies in overcoming resistant disease, with improvements in survival being seen, even in the relapsed and refractory setting (Kumar & Rajkumar 2006; Piazza et al. 2007).